2016
DOI: 10.1093/icc/dtv054
|View full text |Cite
|
Sign up to set email alerts
|

The greener the better? Job creation effects of environmentally-friendly technological change

Abstract: This article investigates the link between environment-related innovation and job creation at firm level. Employing Italian data on 4507 manufacturing firms, matched with patent records for the period 2001-2008, we test whether "green" innovation, measured by the number of environment-related patents, has a positive effect on long-run employment growth that is specific with respect to non-environmental innovation. Results show a strong positive impact of "green" innovation on long-run job creation, substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 63 publications
(69 reference statements)
1
46
1
2
Order By: Relevance
“…On the strength of these previous contributions, we argue that, despite their higher costs (Gagliardi et al 2016), new green technologies could provide firms with 'extra returns' compared to non-green technologies. These extra returns can be exploited (e.g.…”
Section: Background Literature and Research Questionsmentioning
confidence: 87%
See 2 more Smart Citations
“…On the strength of these previous contributions, we argue that, despite their higher costs (Gagliardi et al 2016), new green technologies could provide firms with 'extra returns' compared to non-green technologies. These extra returns can be exploited (e.g.…”
Section: Background Literature and Research Questionsmentioning
confidence: 87%
“…More relevant to our analysis is the patent-based study carried out in Italy (2001Italy ( -2008 by Gagliardi et al (2016), showing that eco-innovator firms have more employment growth than their non-green counterparts. Similarly, Colombelli et al (2015) studied patents of more than 400,000 firms in Germany, France, Italy, Spain and Sweden over the period of 2002-2011 and found that eco-innovation capabilities drive sales growth more than 'generic' ones.…”
Section: Background Literature and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, academics know much less about the potential complementarities between environmental innovation and employment in terms of economic and firms' behavior. In this regard, numerous works focus on the drivers of environmental innovation [2][3][4][5][6], but empirical research about the relationship between environmental innovation and employment is still relatively scarce [7][8][9][10][11][12]. Even though the analysis of influence of eco-innovation on performance still faces relevant theoretical and empirical limitations [13], the current available statistical information allows achieving more insights on drivers and synergies between eco-innovation and employment growth.…”
Section: Introductionmentioning
confidence: 99%
“…A couple of studies recently point out that environmental innovation can be a driver for jobs growth (Licht and Peters 2013), and may even provide more new employment than other types of innovation (Gagliardi, Marin and Miriello 2016). These results may also shed a different light on the relationship between innovation, jobs growth and (environmental) regulation (Vona et al 2015) by pointing to employment gains from regulation.…”
mentioning
confidence: 99%